POTENSI KHASIAT OBAT TANAMAN MARGA PIPER : Piper nigrum L., Piper retrofractum Vahl., Piper betle Linn., Piper cubeba L. dan Piper crocatum Ruiz & Pav - Rain Kihara Boangmanalu; Ade Zuhrotun (Fakultas Farmasi, Universitas Padjadjaran, 2018)
Piper, the genus of Piperaceae family recorded up to date is about 4226 plant species. These plants are widely known as spices, medicinal plants and ornamental plants. The use of Piper plants as an empirical base is widely known in Indonesia. This review was done by collecting the evidence base of efficacy and information from various sources or any kind of literature on the pharmacological activities of several piper plants. The data obtained is then displayed in the form of descriptions and tables. Based on the review, it is known that there are five plants that have the potential to be developed into traditional medicine. Five species of piper genus were Piper nigrum L., Piper retrofractum Vahl, Piper betle Linn, Piper cubeba L. and Piper crocatum Ruiz & Pav have been widely used in empirical usage in the community, have been shown to have enormous benefits based on various studies. In general, pharmacological activities of these five plants are as antibacterial and antifungal. The results of this review can be utilized to further convince the community in the use of five plants as well as the development of raw materials of traditional medicine.